Terazosin and propranolol as blockers to the deleterious effect of nicotine in a random skin flap, in the rat - Fonseca,Andre V. (2004)
PURPOSE: To evaluate the effect of Terazosin and Propranolol on the prevention of necrosis induced by nicotine, in a random skin flap. METHODS: This study utilized 32 adult male Wistar-EPM rats divided, at random, into four groups of eight animals each. All the 32 animals received nicotine (2 mg/kg/day) subcutaneously, for one week before and one week after flap elevation. CG (Control) group received distilled water (0.2 ml/day) by gavage and saline (0.5 ml) intraperitoneally, for seven days in the postoperative period. TG (Terazosin) group received terazosin hydrochloride (3 mg/day) by gavage and saline, intraperitoneally, for seven days in the postoperative period. PG (Propranolol) group received propranolol (1.5 mg/day) intraperitoneally and distilled water, by gavage, following the stablished pattern. TPG (Terazosin + Propranolol) group received both drugs. On the seventh postoperative day, the distal necrotic area of the flaps was determined via the paper template method. Blood and skin samples were collected in order to allow determination of Malondialdehyde (MDA) levels RESULTS: The control group had a mean value of 39.5 % of necrosis; the Terazosin group 25.1 %; the Propranolol group 34.5 % and the Terazosin + Propranolol group 26.2 % of necrosis. MDA levels in the serum and in the skin samples behave similarly, with an exception regarding Propranolol group in this case. CONCLUSION: Terazosin is effective in the prevention of necrosis in this animal model and Propranolol is not effective in this case.